ZnO-based piezoresistive semiconductor ceramic and preparation method and application thereof

CN121850639BActive Publication Date: 2026-10-27ANHUI KEFERMAN NEW MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511976258.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-25
Publication Date
2026-10-27
Estimated Expiration
2045-12-25

AI Technical Summary

Technical Problem

为获得更高的压敏电压梯度和非线性系数,行业趋势是采用更细的ZnO原料和更复杂的多元掺杂体系,但这使得粉末容易团聚,在微观尺度上实现添加剂均匀分布的难度呈指数级增加,烧结过程中容易形成异常长大的晶粒或局部低阻区域,导致生产工艺窗口变窄,对原料一致性、混料工艺和烧结曲线极其敏感

Benefits of technology

1、本发明在ZnO基压敏半导体陶瓷制备过程中添加了二硫键有机硅交联剂,其硅氧烷端能够与ZnO表面键合,形成Si-O-Zn共价键,长链分子形成三维网络,将Bi2O3、MnO2、Co3O4等添加剂均匀包裹在ZnO颗粒界面,解决了传统工艺中添加剂易团聚、分布随机的根本问题;在紫外-近红外双光源照射下,紫外光触发二硫键的可逆交换,使得局部粘度下降,上转换纳米颗粒(UCNPs)吸收近红外光,通过稀土离子交叉弛豫产生热量形成温度梯度,驱动添加剂向高温区迁移,从而实现了添加剂主动分布、可控重排的技术效果;在烧结升温过程中,二硫键分解产生的硫原子氧化为SO2逸出,为阳离子扩散提供通道,其有机骨架随后完全氧化分解为气体挥发,提升了掺杂效率与晶界形成质量,且无碳残留。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a ZnO-based pressure-sensitive semiconductor ceramic and a preparation method and application thereof, and belongs to the technical field of semiconductor ceramics. The ZnO-based pressure-sensitive semiconductor ceramic provided by the application comprises the following components: ZnO, Bi2O3, MnO2, Co3O4, Cr2O3, Sb2O3, Al(NO3)3, a disulfide bond organic silicon crosslinking agent, a light-heat conversion agent, a photoinitiator, a dispersing agent and a solvent. The ZnO-based pressure-sensitive semiconductor ceramic has the characteristics of continuous thickness and uniform composition, and the voltage gradient and the nonlinear coefficient of the ZnO-based pressure-sensitive semiconductor ceramic are superior to those of traditional products; the parameter drift rate of the ZnO-based pressure-sensitive semiconductor ceramic after surge impact is small, and the ZnO-based pressure-sensitive semiconductor ceramic can be applied to high-end application scenes such as new energy automobile on-board chargers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor ceramics technology, specifically relating to a ZnO-based varistor semiconductor ceramic, its preparation method, and its application. Background Technology

[0002] Semiconductor ceramics are a class of functional materials with unique electrical properties; their resistivity can undergo significant and controllable nonlinear changes under external conditions (such as voltage and temperature). Among them, zinc oxide (ZnO)-based varistors are the most widely used and core surge protection materials. Their mechanism of action stems from the "Schottky barrier" formed by additives at the ZnO grain boundaries. Under normal voltage, the barrier exhibits a high resistance state with a small leakage current; when encountering an overvoltage surge, the barrier is instantly broken down, and the resistance drops sharply, thereby dissipating dangerous energy and protecting downstream precision electronic equipment. ZnO varistors are the mainstream overvoltage protection devices globally, especially in emerging and high-reliability fields such as new energy vehicles, renewable energy power generation (photovoltaics, wind power), 5G communication base stations, and industrial frequency converters, where demand is growing rapidly.

[0003] Currently, ZnO varistors generally employ a mixed additive sintering technology, which involves incorporating various oxides into high-purity ZnO powder and then forming a dense ceramic body through high-temperature solid-state sintering. However, this mature process suffers from some inherent defects that are difficult to overcome, directly hindering further improvements in device performance.

[0004] In existing processes, the distribution and migration of additives are dominated by bulk diffusion at high temperatures. This process is influenced by multiple random factors, including the initial agglomeration state of the powder, local compositional fluctuations, and temperature field uniformity. This results in highly random grain boundary barriers at the microscale (between different grain boundaries) – the barrier height, width, and defect state density are uneven. This inhomogeneity leads to batch-to-batch dispersion and batch-to-batch fluctuations in the macroscopic electrical properties of ceramic sheets (such as varistor voltage). Individual devices also exhibit performance weaknesses, limiting the surge energy density (i.e., energy tolerance) that a unit volume of device can stably withstand. Furthermore, in traditional sintering processes, the grain boundary structure forms at high temperatures and becomes a static, rigid structure after cooling. When the device is subjected to multiple surge impacts, the enormous current and Joule heating damage the atomic arrangement and defect states at the grain boundaries, causing irreversible drift in key parameters (such as varistor voltage and leakage current), and gradual degradation of nonlinear characteristics. To achieve higher varistor voltage gradients and nonlinear coefficients, the industry trend is to use finer ZnO raw materials and more complex multi-component doping systems. However, this makes the powder prone to agglomeration, exponentially increasing the difficulty of achieving uniform additive distribution at the microscale. During sintering, abnormally large grains or localized low-resistivity regions are easily formed, leading to a narrowing of the production process window and extreme sensitivity to raw material consistency, mixing processes, and sintering curves. Based on these shortcomings, it is essential to propose a novel ZnO-based varistor semiconductor ceramic. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention proposes a ZnO-based varistor semiconductor ceramic, its preparation method, and its applications.

[0006] The first aspect of this invention is to provide a ZnO-based varistor semiconductor ceramic, comprising the following components in parts by weight: ZnO 95-97 parts, Bi2O3 0.7-0.9 parts, MnO2 0.4-0.5 parts, Co3O4 0.2-0.3 parts, Cr2O3 0.1-0.3 parts, Sb2O3 0.1-0.2 parts, Al(NO3)3 0.05-0.15 parts, disulfide bond organosilicon crosslinking agent 0.4-0.6 parts, photothermal conversion agent 0.1-0.3 parts, photoinitiator 0.03-0.08 parts, dispersant 0.2-0.4 parts, and solvent 140-160 parts; The disulfide bond organosilicon crosslinking agent is prepared by the following steps: (1) Mix 3-mercaptopropyltrimethoxysilane with solvent II, add oxidant solution dropwise to react, and after reaction, neutralize, wash, filter and dry to obtain 3-(thiosulfinate)propyltrimethoxysilane; (2) Under the protection of an inert gas, 3-(thiosulfinate)propyltrimethoxysilane, iodine and sodium bicarbonate were mixed and reacted to remove impurities and obtain bis(trimethoxysilylpropyl) disulfide; (3) Mix bis(trimethoxysilylpropyl) disulfide, allyl magnesium bromide and anhydrous tetrahydrofuran and react to obtain allyl-terminated disulfide; (4) Under the protection of an inert gas, the allyl-terminated disulfide, 2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone and the initiator are mixed and reacted to remove impurities and purify to obtain a disulfide bond organosilicon crosslinking agent.

[0007] It should be noted that this invention creatively synthesizes a photosensitive organosilicon crosslinking agent containing disulfide bonds. Under the action of a catalyst, the thiol group in 3-mercaptopropyltrimethoxysilane is oxidized by hydrogen peroxide to transform into a more reactive thiosulfinate intermediate. This intermediate undergoes oxidative coupling under the action of iodine and sodium bicarbonate, and the two molecules are connected by a newly formed dynamic disulfide bond (-SS-) to form a backbone. Then, through a Grignard reagent exchange reaction, the methoxy group at the end of the backbone is replaced with allyl magnesium bromide to introduce a reactive allyl group, providing a site for subsequent grafting. Finally, under the action of a photoinitiator and ultraviolet light, the thiol-containing photosensitive molecule (2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone) reacts with the allyl group, thereby covalently grafting the ultraviolet photosensitive group onto the backbone, ultimately obtaining a multifunctional crosslinking agent that combines siloxane bonding ability, dynamic disulfide bonds, and ultraviolet light response.

[0008] In some embodiments, the oxidant solution is a mixture of hydrogen peroxide, glacial acetic acid, and anhydrous ethanol in a mass ratio of 30:1-3:24-26, with the concentration of hydrogen peroxide being 28-32 wt%; the mass ratio of 3-mercaptopropyltrimethoxysilane to the oxidant solution is 3-3.3:2.8-3; the second solvent is selected from at least one of anhydrous ethanol and methanol, and the mass of the second solvent is 2-3 times the mass of 3-mercaptopropyltrimethoxysilane.

[0009] In some embodiments, the mass ratio of 3-(thiosulfinyl)propyltrimethoxysilane to iodine is 1:0.6-0.75; the equivalent ratio of iodine to sodium bicarbonate is 0.5:1-1.3; and the ratio of bis(trimethoxysilyl)disulfide, allyl magnesium bromide, and anhydrous tetrahydrofuran is 1g:15-20mL:5-10mL.

[0010] In some embodiments, the mass ratio of allyl-terminated disulfide, 2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone and initiator is 1:2.5-3:0.02-0.03; the initiator is selected from at least one of azobisisobutyronitrile and azobisisoheptanenitrile.

[0011] In some embodiments, in step (1), the dropping temperature is <5°C and the reaction is carried out at 18-22°C for 10-14 hours; in step (2), the reaction is carried out at 0-5°C for 30-60 minutes; in step (3), the reaction is carried out at room temperature for 4-6 hours; in step (4), the reaction is carried out under ultraviolet light irradiation at room temperature for 2-4 hours.

[0012] A second aspect of this invention provides a method for preparing ZnO-based varistor semiconductor ceramics, comprising the following steps: S1: ZnO is mixed with solvent 1 to obtain ZnO slurry; Bi2O3, MnO2, Co3O4, Cr2O3, Sb2O3, Al(NO3)3 are mixed with dispersant to obtain suspension; S2: Mix the suspension and ZnO slurry, add disulfide bond organosilicon crosslinking agent and photoinitiator, and perform ultraviolet irradiation treatment. After the treatment, add photothermal conversion agent to react and obtain ZnO-based hybrid slurry. S3: The ZnO-based hybrid slurry is cast and shaped, and then subjected to three stages of irradiation to obtain a green ceramic sheet. The green ceramic sheet is then sintered to obtain the ZnO-based varistor semiconductor ceramic.

[0013] In some embodiments, the photothermal conversion agent is UCNPs with an excitation wavelength of 980 nm or 808 nm; the dispersant is selected from at least one of polyvinylpyrrolidone and polyvinyl butyral; the photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate; and the solvent is a mixture of ethanol and water in a volume ratio of 7:3.

[0014] UCNPs stands for NaYF4:Yb,Er@NaYF4 core-shell upconversion nanoparticles.

[0015] In some embodiments, the aspect ratio of ZnO is 3-5:1; the diameters of Bi2O3, MnO2, Co3O4, Cr2O3 and Sb2O3 are all 20-30 nm.

[0016] In some embodiments, in S2, the ultraviolet irradiation treatment is performed at a wavelength of 365 nm and a power density of 45-55 mW / cm². 2 Irradiation for 25-35 minutes followed by stirring for 8-12 minutes under light-protected conditions; in S3, the three-stage irradiation includes: Stage 1: using a power density of 25-35 mW / cm³. 2 Phase 1: Ultraviolet irradiation for 3-8 minutes; Phase 2: Near-infrared irradiation 8-12 times at a laser power of 1.8-2.2W and a scanning speed of 8-12mm / s; Phase 3: Using a power density of 75-85mW / cm². 2 Expose to ultraviolet light for 8-12 minutes.

[0017] The third aspect of this invention is to provide an application of ZnO-based varistor ceramics in the field of on-board chargers for new energy vehicles.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention adds a disulfide bond organosilicon crosslinking agent during the preparation of ZnO-based varistor ceramics. The siloxane end of the agent can bond with the ZnO surface to form Si-O-Zn covalent bonds. The long-chain molecules form a three-dimensional network, uniformly coating additives such as Bi2O3, MnO2, and Co3O4 onto the ZnO particle interface, solving the fundamental problem of easy agglomeration and random distribution of additives in traditional processes. Under ultraviolet-near-infrared dual-source irradiation, ultraviolet light triggers the reversible exchange of disulfide bonds, resulting in a decrease in local viscosity. Upconversion nanoparticles (UCNPs) absorb near-infrared light and generate heat through rare earth ion cross-relaxation, forming a temperature gradient that drives the additives to migrate to the high-temperature region, thereby achieving the technical effect of active distribution and controllable rearrangement of additives. During the sintering heating process, the sulfur atoms generated by the decomposition of disulfide bonds are oxidized to SO2 and released, providing a channel for cation diffusion. The organic framework is then completely oxidized and decomposed into gas volatilization, improving the doping efficiency and grain boundary formation quality, and leaving no carbon residue.

[0019] 2. The ZnO-based varistor ceramic prepared by this invention has the characteristics of continuous thickness and uniform composition. Its voltage gradient and nonlinear coefficient are superior to those of traditional products, and the energy absorption capacity per unit volume of ceramic is also improved. In addition, it has excellent durability and stability, and the parameter drift rate after surge impact is small. It can be applied to high-end application scenarios such as on-board chargers for new energy vehicles. Detailed Implementation

[0020] The present invention will now be described in further detail with reference to specific embodiments.

[0021] Example 1 A ZnO-based varistor semiconductor ceramic comprises the following components in parts by weight: 96 parts ZnO, 0.8 parts Bi2O3, 0.45 parts MnO2, 0.25 parts Co3O4, 0.2 parts Cr2O3, 0.15 parts Sb2O3, 0.1 parts Al(NO3)3, 0.5 parts disulfide bond organosilicon crosslinking agent, 0.2 parts photothermal conversion agent, 0.05 parts photoinitiator, 0.3 parts dispersant, and 150 parts solvent; The disulfide bond organosilicon crosslinking agent is prepared by the following steps: (1) 3-mercaptopropyltrimethoxysilane was mixed with anhydrous ethanol and oxidized at <5°C. The reaction was carried out at 20°C for 12 h. After the reaction, the mixture was neutralized, washed, filtered, and dried to obtain 3-(thiosulfinyl)propyltrimethoxysilane. The oxidizing agent solution was composed of 30wt% hydrogen peroxide, glacial acetic acid and anhydrous ethanol in a mass ratio of 30:2:25. The mass ratio of 3-mercaptopropyltrimethoxysilane to the oxidizing agent solution was 3.15:2.9. The mass of anhydrous ethanol was 2.5 times the mass of 3-mercaptopropyltrimethoxysilane. (2) Under inert gas protection, 3-(thiosulfinyl)propyltrimethoxysilane, iodine and sodium bicarbonate were mixed and reacted at 2°C for 45 min to remove impurities and obtain bis(trimethoxysilylpropyl) disulfide; wherein, the mass ratio of 3-(thiosulfinyl)propyltrimethoxysilane to iodine was 1:0.7, and the equivalent ratio of iodine to sodium bicarbonate was 0.5:1.15; (3) Mix bis(trimethoxysilylpropyl) disulfide, allyl magnesium bromide and anhydrous tetrahydrofuran in a ratio of 1g:18mL:8mL and react at room temperature for 5h to obtain allyl-terminated disulfide; (4) Under inert gas protection, allyl-terminated disulfide, 2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone and azobisisobutyronitrile were mixed in a mass ratio of 1:2.8:0.025 and reacted at room temperature for 3 hours under ultraviolet light irradiation to remove impurities and purify to obtain disulfide bond organosilicon crosslinking agent.

[0022] The above-mentioned ZnO-based varistor ceramic was prepared by the following steps: S1: ZnO is mixed with solvent one to obtain ZnO slurry; Bi2O3, MnO2, Co3O4, Cr2O3, Sb2O3, Al(NO3)3 and polyvinylpyrrolidone are mixed to obtain suspension; wherein, solvent one is a mixture of ethanol and water in a volume ratio of 7:3, the aspect ratio of ZnO is 4:1, and the diameters of Bi2O3, MnO2, Co3O4, Cr2O3 and Sb2O3 are all 25nm; S2: Mix the suspension and ZnO slurry, add disulfide-bonded organosilicon crosslinking agent and 2-hydroxy-2-methyl-1-phenyl-1-propanone, and heat at a wavelength of 365 nm and a power density of 50 mW / cm². 2 Irradiated for 30 min, and after irradiation, UCNPs with an excitation wavelength of 808 nm (source: Xi'an Qiyue Biotechnology) were added. The mixture was stirred for 10 min under light-protected conditions to obtain ZnO-based hybrid slurry. S3: The ZnO-based hybrid slurry is cast and shaped, and then subjected to three-stage irradiation to obtain a green ceramic sheet. The green ceramic sheet is then sintered to obtain the ZnO-based varistor semiconductor ceramic. The three-stage irradiation is as follows: Stage 1: Using a power density of 30mW / cm³2 Phase 1: Ultraviolet irradiation for 5 minutes; Phase 2: Near-infrared irradiation 10 times at a scanning speed of 10 mm / s with a laser power of 2W; Phase 3: Using a power density of 80 mW / cm². 2 Irradiate with ultraviolet light for 10 minutes.

[0023] The ZnO-based varistor ceramics prepared by the above steps can be used in the field of on-board chargers for new energy vehicles.

[0024] Example 2 A ZnO-based varistor semiconductor ceramic comprises the following components in parts by weight: 97 parts ZnO, 0.9 parts Bi2O3, 0.5 parts MnO2, 0.3 parts Co3O4, 0.3 parts Cr2O3, 0.2 parts Sb2O3, 0.15 parts Al(NO3)3, 0.6 parts disulfide bond organosilicon crosslinking agent, 0.3 parts photothermal conversion agent, 0.08 parts photoinitiator, 0.4 parts dispersant, and 160 parts solvent; The disulfide bond organosilicon crosslinking agent is prepared by the following steps: (1) 3-mercaptopropyltrimethoxysilane was mixed with methanol and oxidized at <5°C. The reaction was carried out at 22°C for 10 h. After the reaction, the mixture was neutralized, washed, filtered and dried to obtain 3-(thiosulfinate)propyltrimethoxysilane. The oxidizing agent solution was composed of 32wt% hydrogen peroxide, glacial acetic acid and anhydrous ethanol in a mass ratio of 30:3:26. The mass ratio of 3-mercaptopropyltrimethoxysilane to oxidizing agent solution was 3.3:3. The mass of methanol was 3 times the mass of 3-mercaptopropyltrimethoxysilane. (2) Under inert gas protection, 3-(thiosulfinyl)propyltrimethoxysilane, iodine and sodium bicarbonate were mixed and reacted at 5°C for 30 min to remove impurities and obtain bis(trimethoxysilylpropyl) disulfide; wherein, the mass ratio of 3-(thiosulfinyl)propyltrimethoxysilane to iodine was 1:0.75; and the equivalent ratio of iodine to sodium bicarbonate was 0.5:1.3; (3) Mix bis(trimethoxysilylpropyl) disulfide, allyl magnesium bromide and anhydrous tetrahydrofuran in a ratio of 1g:20mL:10mL and react at room temperature for 6h to obtain allyl-terminated disulfide; (4) Under inert gas protection, allyl-terminated disulfide, 2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone and azobisisoheptanenitrile were mixed in a mass ratio of 1:3:0.03 and reacted at room temperature for 4 hours under ultraviolet light irradiation to remove impurities and purify to obtain disulfide bond organosilicon crosslinking agent.

[0025] The above-mentioned ZnO-based varistor ceramic was prepared by the following steps: S1: ZnO is mixed with solvent one to obtain ZnO slurry; Bi2O3, MnO2, Co3O4, Cr2O3, Sb2O3, Al(NO3)3 and polyvinyl butyral are mixed to obtain suspension; wherein, solvent one is a mixture of ethanol and water in a volume ratio of 7:3, the aspect ratio of ZnO is 5:1, and the diameters of Bi2O3, MnO2, Co3O4, Cr2O3 and Sb2O3 are all 30nm; S2: Mix the suspension and ZnO slurry, add a disulfide-bonded organosilicon crosslinking agent and ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and heat at a wavelength of 365 nm and a power density of 55 mW / cm². 2 After irradiation for 35 min, UCNPs with an excitation wavelength of 980 nm were added (Source: Xi'an Qiyue Biotechnology). The mixture was stirred for 12 min under light-protected conditions to obtain ZnO-based hybrid slurry. S3: The ZnO-based hybrid slurry is cast and shaped, and then subjected to three-stage irradiation to obtain a green ceramic sheet. The green ceramic sheet is then sintered to obtain the ZnO-based varistor semiconductor ceramic. The three-stage irradiation is as follows: Stage 1: Using a power density of 35 mW / cm². 2 Phase 1: Ultraviolet irradiation for 8 minutes; Phase 2: Near-infrared irradiation 12 times at a scanning speed of 12 mm / s with a laser power of 2.2 W; Phase 3: Using a power density of 85 mW / cm². 2 Irradiate with ultraviolet light for 12 minutes.

[0026] The ZnO-based varistor ceramics prepared by the above steps can be used in the field of on-board chargers for new energy vehicles.

[0027] Example 3 A ZnO-based varistor semiconductor ceramic comprises the following components in parts by weight: 95 parts ZnO, 0.7 parts Bi2O3, 0.4 parts MnO2, 0.2 parts Co3O4, 0.1 parts Cr2O3, 0.1 parts Sb2O3, 0.05 parts Al(NO3)3, 0.4 parts disulfide bond organosilicon crosslinking agent, 0.1 parts photothermal conversion agent, 0.03 parts photoinitiator, 0.2 parts dispersant, and 140 parts solvent. The disulfide bond organosilicon crosslinking agent is prepared by the following steps: (1) 3-mercaptopropyltrimethoxysilane was mixed with anhydrous ethanol and oxidized at <5°C. The reaction was carried out at 18°C ​​for 14 h. After the reaction, the mixture was neutralized, washed, filtered and dried to obtain 3-(thiosulfinyl)propyltrimethoxysilane. The oxidizing agent solution was composed of 32wt% hydrogen peroxide, glacial acetic acid and anhydrous ethanol in a mass ratio of 30:1:24. The mass ratio of 3-mercaptopropyltrimethoxysilane to the oxidizing agent solution was 3:2.8. The mass of anhydrous ethanol was twice the mass of 3-mercaptopropyltrimethoxysilane. (2) Under inert gas protection, 3-(thiosulfinyl)propyltrimethoxysilane, iodine and sodium bicarbonate were mixed and reacted at 0°C for 60 min to remove impurities and obtain bis(trimethoxysilylpropyl) disulfide; wherein, the mass ratio of 3-(thiosulfinyl)propyltrimethoxysilane to iodine was 1:0.6; and the equivalent ratio of iodine to sodium bicarbonate was 0.5:1; (3) Mix bis(trimethoxysilylpropyl) disulfide, allyl magnesium bromide and anhydrous tetrahydrofuran in a ratio of 1g:15mL:5mL and react at room temperature for 4h to obtain allyl-terminated disulfide. (4) Under inert gas protection, allyl-terminated disulfide, 2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone and azobisisobutyronitrile were mixed in a mass ratio of 1:2.5:0.02 and reacted at room temperature for 2 hours under ultraviolet light irradiation to remove impurities and purify to obtain disulfide bond organosilicon crosslinking agent.

[0028] The above-mentioned ZnO-based varistor ceramic was prepared by the following steps: S1: ZnO is mixed with solvent one to obtain ZnO slurry; Bi2O3, MnO2, Co3O4, Cr2O3, Sb2O3, Al(NO3)3 and polyvinylpyrrolidone are mixed to obtain suspension; wherein, solvent one is a mixture of ethanol and water in a volume ratio of 7:3, the aspect ratio of ZnO is 3:1, and the diameters of Bi2O3, MnO2, Co3O4, Cr2O3 and Sb2O3 are all 20nm; S2: Mix the suspension and ZnO slurry, add disulfide-bonded organosilicon crosslinking agent and 2-hydroxy-2-methyl-1-phenyl-1-propanone, and heat at a wavelength of 365 nm and a power density of 45 mW / cm². 2 After irradiation for 35 min, UCNPs with an excitation wavelength of 808 nm were added (Source: Xi'an Qiyue Biotechnology). The mixture was stirred for 8 min under light-protected conditions to obtain ZnO-based hybrid slurry. S3: The ZnO-based hybrid slurry is cast and shaped, and then subjected to three-stage irradiation to obtain a green ceramic sheet. The green ceramic sheet is then sintered to obtain the ZnO-based varistor semiconductor ceramic. The three-stage irradiation is as follows: Stage 1: Using a power density of 35 mW / cm². 2 Phase 1: Ultraviolet irradiation for 3 minutes; Phase 2: Near-infrared irradiation 8 times at a scanning speed of 8 mm / s under a laser power of 2.2W; Phase 3: Using a power density of 85 mW / cm². 2 Irradiate with ultraviolet light for 8 minutes.

[0029] The ZnO-based varistor ceramics prepared by the above steps can be used in the field of on-board chargers for new energy vehicles.

[0030] Example 4 The composition is basically the same as in Example 1, except that the ZnO-based varistor ceramic comprises the following components in parts by weight: 97 parts ZnO, 0.75 parts Bi2O3, 0.5 parts MnO2, 0.2 parts Co3O4, 0.25 parts Cr2O3, 0.2 parts Sb2O3, 0.15 parts Al(NO3)3, 0.45 parts disulfide bond organosilicon crosslinking agent, 0.15 parts photothermal conversion agent, 0.04 parts photoinitiator, 0.25 parts dispersant, and 145 parts solvent.

[0031] Example 5 The composition is basically the same as in Example 1, except that the ZnO-based varistor ceramic comprises the following components in parts by weight: 95 parts ZnO, 0.85 parts Bi2O3, 0.4 parts MnO2, 0.3 parts Co3O4, 0.25 parts Cr2O3, 0.2 parts Sb2O3, 0.05 parts Al(NO3)3, 0.55 parts disulfide bond organosilicon crosslinking agent, 0.25 parts photothermal conversion agent, 0.06 parts photoinitiator, 0.35 parts dispersant, and 155 parts solvent.

[0032] Comparative Example 1 It is basically the same as Example 1, except that the disulfide bond organosilicon crosslinking agent is replaced with the same amount of silane coupling agent KH-550.

[0033] Comparative Example 2 This is essentially the same as Example 1, except that the three-stage irradiation is replaced with a power density of 30 mW / cm². 2 Irradiate with ultraviolet light for 20 minutes, followed by a power density of 80 mW / cm². 2 Irradiate with ultraviolet light for 10 minutes.

[0034] Comparative Example 3 It is basically the same as Example 1, except that no photothermal conversion agent is added.

[0035] The performance of the ZnO-based varistor ceramics prepared in Examples 1-5 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1.

[0036] Electrical performance testing: Varistor voltage: At 25℃, apply a DC current of 1mA and measure the voltage across the sample. Varistor voltage gradient = V1mA / sample thickness; Nonlinear coefficient (α): Measure the voltages V1 and V2 at 0.1mA (I1) and 1mA (I2) and calculate using the formula α = 1 / log(V2 / V1); Reliability and lifespan testing: Surge current lifespan test: Apply an 8 / 20μs pulse of rated energy (e.g., 75% Wmax) every 5 minutes, record the change in V1mA until the change exceeds ±10%, and record the number of pulses; High temperature load lifespan test: Under a 125℃ environment and a DC voltage of 0.85 times V1mA, continuously load for 1000 hours, measure V1mA and I_L at regular intervals, and calculate their rate of change.

[0037] Table 1 As shown in Table 1, the ZnO-based varistor ceramic provided in this embodiment of the invention is significantly superior to the comparative examples in terms of performance, exhibiting excellent electrical properties, durability, and stability. Comparing the comparative examples, it can be seen that Comparative Example 1 lacks a disulfide bond organosilicon crosslinking agent, failing to form a reversible exchange dynamic covalent network. During sintering, the migration of additives (Bi2O3, etc.) relies entirely on random bulk diffusion. Elements such as Bi agglomerate discontinuously at grain boundaries, failing to form a uniform interface, resulting in low varistor voltage, poor nonlinear coefficient, and surge energy concentrated at a few "weak" grain boundaries, leading to localized overheating and breakdown, resulting in low overall tolerance. Comparative Example 2 only uses ultraviolet irradiation, lacking the localized high temperature and temperature gradient generated by near-infrared light as a driving force for migration, forming uniform but low-concentration grain boundary doping, resulting in limited improvement in varistor voltage and nonlinear coefficient. Comparative Example 3 does not add a near-infrared photothermal conversion agent, preventing the grain boundary region from obtaining localized high temperatures. Uniform heating cannot specifically repair areas prone to defects, such as grain boundary junctions. These microscopic defects easily degrade performance under repeated surges or high temperatures.

[0038] The above descriptions are merely some embodiments of the present invention. Those skilled in the art can make various modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the scope of protection of the present invention.

Claims

1. A method for preparing ZnO-based varistor semiconductor ceramics, characterized in that, Includes the following steps: S1: ZnO is mixed with solvent 1 to obtain ZnO slurry; Bi2O3, MnO2, Co3O4, Cr2O3, Sb2O3, Al(NO3)3 are mixed with dispersant to obtain suspension; S2: Mix the suspension and the ZnO slurry, add a disulfide bond organosilicon crosslinking agent and a photoinitiator, and perform the reaction at a wavelength of 365 nm and a power density of 45-55 mW / cm². 2 After irradiation for 25-35 minutes, a photothermal conversion agent was added and the mixture was stirred for 8-12 minutes under light-protected conditions to obtain a ZnO-based hybrid slurry. S3: The ZnO-based hybrid slurry is cast and shaped, and then subjected to three-stage irradiation to obtain a green ceramic sheet. The green ceramic sheet is then sintered to obtain the ZnO-based varistor semiconductor ceramic. The three-stage irradiation includes: Stage 1: using a power density of 25-35 mW / cm². 2 Phase 1: Ultraviolet irradiation for 3-8 minutes; Phase 2: Near-infrared irradiation 8-12 times at a laser power of 1.8-2.2W and a scanning speed of 8-12mm / s; Phase 3: Using a power density of 75-85mW / cm². 2 Irradiate with ultraviolet light for 8-12 minutes; The ZnO-based varistor ceramic comprises the following components in parts by weight: ZnO 95-97 parts, Bi2O3 0.7-0.9 parts, MnO2 0.4-0.5 parts, Co3O4 0.2-0.3 parts, Cr2O3 0.1-0.3 parts, Sb2O3 0.1-0.2 parts, Al(NO3)3 0.05-0.15 parts, disulfide bond organosilicon crosslinking agent 0.4-0.6 parts, photothermal conversion agent 0.1-0.3 parts, photoinitiator 0.03-0.08 parts, dispersant 0.2-0.4 parts, and solvent 140-160 parts; the photothermal conversion agent is UCNPs with an excitation wavelength of 980nm or 808nm. The disulfide bond organosilicon crosslinking agent is prepared by the following steps: (1) Mix 3-mercaptopropyltrimethoxysilane with solvent II, add oxidant solution dropwise to react, and after reaction, neutralize, wash, filter and dry to obtain 3-(thiosulfinate)propyltrimethoxysilane; (2) Under the protection of an inert gas, the 3-(thiosulfinate)propyltrimethoxysilane, iodine and sodium bicarbonate are mixed and reacted to remove impurities to obtain bis(trimethoxysilylpropyl) disulfide; (3) The bis(trimethoxysilylpropyl) disulfide, allyl magnesium bromide and anhydrous tetrahydrofuran are mixed and reacted to obtain an allyl-terminated disulfide; (4) Under the protection of an inert gas, the allyl-terminated disulfide, 2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone and the initiator are mixed and reacted to remove impurities and purify to obtain the disulfide bond organosilicon crosslinking agent.

2. The method for preparing ZnO-based varistor semiconductor ceramics according to claim 1, characterized in that, The oxidant solution is composed of hydrogen peroxide, glacial acetic acid, and anhydrous ethanol in a mass ratio of 30:1-3:24-26, wherein the concentration of hydrogen peroxide is 28-32 wt%; the mass ratio of 3-mercaptopropyltrimethoxysilane to the oxidant solution is 3-3.3:2.8-3; the second solvent is selected from at least one of anhydrous ethanol and methanol, and the mass of the second solvent is 2-3 times the mass of the 3-mercaptopropyltrimethoxysilane.

3. The method for preparing ZnO-based varistor semiconductor ceramics according to claim 1, characterized in that, The mass ratio of 3-(thiosulfinyl)propyltrimethoxysilane to iodine is 1:0.6-0.75; the ratio of bis(trimethoxysilyl)disulfide, allyl magnesium bromide, and anhydrous tetrahydrofuran is 1g:15-20mL:5-10mL.

4. The method for preparing ZnO-based varistor semiconductor ceramics according to claim 1, characterized in that, The mass ratio of the allyl-terminated disulfide, the 2-hydroxy-4'-(3-mercaptopropoxy)-benzophenone, and the initiator is 1:2.5-3:0.02-0.03; the initiator is selected from at least one of azobisisobutyronitrile and azobisisoheptanenitrile.

5. The method for preparing ZnO-based varistor semiconductor ceramics according to claim 1, characterized in that, In step (1), the dropping temperature is <5℃, and the reaction is carried out at 18-22℃ for 10-14h; in step (2), the reaction is carried out at 0-5℃ for 30-60min; in step (3), the reaction is carried out at room temperature for 4-6h; in step (4), the reaction is carried out at room temperature under ultraviolet light irradiation for 2-4h.

6. The method for preparing ZnO-based varistor semiconductor ceramics according to claim 1, characterized in that, The dispersant is selected from at least one of polyvinylpyrrolidone and polyvinyl butyral; the photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate; the solvent is a mixture of ethanol and water in a volume ratio of 7:

3.

7. The method for preparing ZnO-based varistor semiconductor ceramics according to claim 1, characterized in that, The aspect ratio of the ZnO is 3-5:1; the diameters of the Bi2O3, MnO2, Co3O4, Cr2O3 and Sb2O3 are all 20-30 nm.

8. A ZnO-based varistor semiconductor ceramic, prepared by the preparation method according to any one of claims 1-7.

9. The application of the ZnO-based varistor semiconductor ceramic of claim 8 in the field of on-board chargers for new energy vehicles.

Citation Information

Patent Citations

  • Zinc oxide varistor based on ZnO coated SiO2 core-shell structure and preparation method thereof

    CN114605143A

  • Photocuring 3D printing biological ceramic material and preparation method thereof

    CN121135401A